Investigation Aging Behavior of High Energy Propellant Materials. (March 2019) - Yan, Gu; Liu, Wenliang; Wang, Qiong; Du, Jiaojiao; Wang, Fangfang; Yu, Silong
Abstract: NEPE propellants were exposed to aging at 55°C, 65°C, 70°C, and 75°C, respectively. The relative contents of stabilizer (MNA), tensile strength and are measured to analysis the aging characteristic of NEPE propellants. Based on aging mechanism of the stabilization depletion and the physical aging properties of NEPE propellants, the whole aging process can be separated into two processes: stabilizer gradual degradation at first stage (chemical aging stage) and degradation reaction of polymer at seconded stage. The stabilizer degradation occurred in the first process, therefore the storage life prediction at normal temperature for NEPE propellant ought to be based on the first process during high temperature aging stage. The storage life of the NEPE propellant at room temperature has been evaluated via Arrhenius and Berthelot approach.